Rekayasa Mesin Resin Transformer Moulding (RTM) sebagai Mesin Mencetak Spesimen Komposit - Siswanto; Teguh Wiyono; Deni Kustianto (Politeknosains, 2017)
RTM engine engineering (Resin Transfer Molding) is aimed to improve the quality of composite materials research in the environment Pratama Mulia Polytechnic Surakarta. Activities of this RTM engine engineering include: Planning, manufacturing, and testing of machinery. making a printing machine with a vacuum method. Material construction machine using steel elbow 50x50 mm, Motor vacuum using Ve280n model with 110-220V / 50-60Hz power 1 HP, Mold using material Allumunium 350 x 350 x 50 mm. After doing the testing machine, it was found that the RTM machine can be used to print fiber-reinforced polyester resin composite with a size of 200 x 200 x 3.2 mm.